Exploring the tolerance of Iraqi wheat varieties: Evaluating seed germination and early growth of six Iraqi wheat varieties under salinity stress - Hameed, Rawad Khalaf; Abd, Ayman Adwan; Ahmed, Noor Maath (Journal of Plant Stress Physiology, 2023)
Abiotic stresses reduce the production of crops by 50% which significantly affects the food security globally. Plant growth and development are affected by salinity stress, Salt stress affects about 19.5% of irrigated lands and 2.1% of drylands which is expected to rise in the future. Wheat Triticum aestivum is classified as one of the most significant crop globally besides maize and rice which significantly contribute as a part of daily calories and proteins and it ranked first for its values in domestication and staple food. The purpose of the study was to assess how well various wheat genotypes tolerated salinity under various salinity concentrations, and the varieties were (Iba99, Hadbaa, Hashmiaa, Al-Rasheed, Sham, and Rabiaa). Different NaCl concentrations were used (50, 100, 150, and 200 mM) and Measurements were made on germination %, shoot length, fresh weight, and dried weight. Iba99, Sham and Rabiaa were the best varieties where the seed germination was 100% and other varieties differed slightly (Hadbaa 40, Hashmiaa 80 and Al-Rasheed 60%). The growth parameters results demonstrated that all the shoot lengths and fresh and dry weights were affected by the salinity stress and the correlation was inverse. It was decreased with the NaCl concentration increase. Rabiaa and Iba99 were the more tolerant and demonstrated high growth under salinity whereas Sham showed lowest growth under salinity.